2022
DOI: 10.1186/s12931-022-02140-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in adult asthma and COPD therapy: a systematic review

Abstract: Background Although asthma is more prevalent in women and the prevalence of COPD is increasing in women, the current international recommendations for the management and prevention of asthma and COPD provide no sex-related indication for the treatment of these diseases. Therefore, we systematically reviewed the evidence across literature on the sex-related effectiveness of asthma and COPD therapy. Methods This systematic review has been registered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 82 publications
1
2
0
Order By: Relevance
“…Compared to men, women had a significantly higher prevalence of asthma (OR 1.93, 95% CI 1.46 to 2.57, p <0.001), and these findings are consistent with those of other studies [ 26 , 27 ]. A recent systematic review of sex differences in adult asthma and COPD also found that asthma is more prevalent among women [ 27 ]. Moreover, the prevalence of asthma was not associated with a higher risk of mortality among men and women in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Compared to men, women had a significantly higher prevalence of asthma (OR 1.93, 95% CI 1.46 to 2.57, p <0.001), and these findings are consistent with those of other studies [ 26 , 27 ]. A recent systematic review of sex differences in adult asthma and COPD also found that asthma is more prevalent among women [ 27 ]. Moreover, the prevalence of asthma was not associated with a higher risk of mortality among men and women in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Major classes of inhaled medications for COPD include long-acting muscarinic antagonists (LAMA), long-acting beta agonists (LABA), combination LABA-LAMA, and combination inhaled corticosteroid (ICS)-LABA. A recent systematic review of randomized controlled trials and observational studies found that there is limited data directly comparing treatment effectiveness between sexes in COPD; however, there is evidence from retrospective and sub-group analyses of large randomized controlled trials ( 57 ). When clinical trials report sex-differences, they are frequently not found; however, some trials may not be powered to detect differences in treatment response between females and males.…”
Section: Copd Therapiesmentioning
confidence: 99%
“…In general, as individuals age, the likelihood of developing the condition increases [1,15], and diagnostic and therapeutic approaches vary depending on sociodemographic factors (sex, gender, or age) [8][9][10][11][12][13][16][17][18][19]. For example, although women tend to exhibit more severe symptoms of COPD than men throughout their lifespan [13], they may also respond better to specific treatments [9].…”
Section: Introductionmentioning
confidence: 99%